Tourism Supply as a Catalyst of Tourism Development in Bishnupur District, Manipur - Hussain, Shabina; Ahmad, Ateeque (National Geographical Journal of India, 2022)
Tourism industry plays a key role for the development of any region where it has immense beauties that may be natural or man-made. It can offer diverse job opportunities to boost the other economic activities. Economic activities can be developed through the development of tourism products include: transportation services, marketing system, accommodation services, communication system, entertainment, recreation and many more; and these are interlinked with the financial influx of the nation. Tourism industry is drivenwith the physical, cultural, religious, and historical attractionsat each and every destination region. With these immense potential of attraction the backward and geographically isolated North-eastern region has a lot of opportunities to develop tourism industry by increasing the opportunities for employment and boost up their economy. Attractions and the allied economic activities of tourism industry are the fundamental elements for tourism development which has been considered as tourism supply at the destination. Bishnupur district is one of the smallest districts of the isolated and backward state Manipur having potential of physical, cultural, religious and historical attractions but it has not been develop due to the inadequacy of its basic elements. The study explored the attractiveness evaluation of nine tourist regions and examined the availability of tourism infrastructure at the destination by using observation method and schedule method through visitors as respondents during field visit. Principal component analysis method has been used to analyze the motivational factors of destination region and arbitrarymethod has also been used. The findings of the study highlight the various tourism attraction activities and also discovered the various suggestive features for the promotion of tourism industry.